Intersectional Approach in Social Inequality Research: Group Project - Ella Mikhaylovna Zhesko; Leonid Nikolaevich Petrukhin (Интеракция. Интервью. Интерпретация)
This article represents the results of an educational project aimed at testing the possibilities of an intersectional approach to describe the matrix of social inequality in the Russian context. Through an analysis of the narratives of eight informants belonging to potentially discriminated groups, the authors attempted to trace the connection between multidirectional vectors of discrimination in their life experiences. As a result, the boundaries of applicability of intersectional analysis were outlined, its methodological advantages and disadvantages were indicated, research reflection on the experience of using the concept was given, as well as recommendations for the further development of the educational project.Comparing the results of the work of colleagues, the authors came to the conclusion that the picture of a complex interweaving of hierarchy mechanisms in the cases considered often represented an “interlacement” of a key parameter of discrimination with a number of secondary ones, which created a complex, individualized pattern of stratification, deepened in the context of a specific social situation.A significant limitation of the intersectional approach is its dependence on context. The applicability of a structured interview for the implementation of this task within the framework of an intersectional approach also seems problematic. The authors of the reviewed texts analyzed the experience of one or two informants which is not enough to draw conclusions about the systemic nature of the detected problems. A larger sample of works should be used or other methods should be used, such as deepening existing information through the use of biographical interviews.This article presents the results of a group educational project conducted with the participation of a team of authors on the initiative of Elena Yuryevna Rozhdestvenskaya as part of the course “Biographical Method in Sociology” of the master’s program “Complex Social Analysis” of the Higher School of Economics.